PENGARUH PENERAPAN AKUNTANSI BERBASIS AKRUAL, PENGAWASAN INTERN, DAN INTERGOVERMENTAL REVENUE TERHADAP KINERJA KEUANGAN DENGAN UKURAN PEMERINTAH DAERAH SEBAGAI VARIABEL INTERVENING - Sunardi Sunardi (Universitas Indo Global Mandiri)
The purpose of this study to empirically examine the effect of the application of accrual accounting, internal oversight and Intergovermental revenue, positive and significant impact on financial performance through the variable size of local government. The observations in this study conducted in local government consisting of: from 11 counties and four cities and the government of South Sumatra Province. The data collection is done by observation on secondary data Budget Revenue and Expenditure in 2009 s.d, 2015.Data processing was performed using the program eviews data analysis technique used is multiple linear regression. Based on the variable application of accrual accounting is negative and significant impact on the size of local government, variable size Intergovermental internal control and revenue have positive and significant impact on the size of local government.Variable size of local government has a negative and significant impact on the ratio of self-reliance and economic ratios, while the size of the local government has a positive and significant impact on the effectiveness ratio and efficiency ratioKey words: Accrual Based Accounting, Internal Control, the Intergovernmental Revenue and financial performance (independence ratio, effectiveness ratio, efficiency ratio and economically ratio